Role of Digital Marketing in Consumer Goods Retailing: Evidence from Vietnam In the Context of the 4th Industrial Revolution - PHAM, CUONG HUNG (The journal of contemporary issues in business and government, 2021)
The development of the 4th Industrial revolution has brought many changes in technologies that are set to change the business world. In Vietnam, retailers of consumer products have taken the advantage of the innovation to engage in digital marketing. The aim of this study is therefore to evaluate the significance of digital marketing in consumer goods retailing. The hypothesis developed for the research is that there is a certain link between digital marketing and consumer goods industry. To achieve its aim, the study uses quantitative research methodologies where data is collected through online questionnaires. A purposive sample of 580 respondents was used to obtain data. The information gathered was analyzed using Ms. Excel and SPSS packages. The study finds that most respondents knew about online sale of consumer goods through advertising ads on the web. The paper then draws a correlation between knowledge of marketing and the actual buying of goods. It is further established that majority of participants prefer buying goods online because it is convenient and cost-effective. The role of digital marketing in consumer goods retailing is explicitly outlined and linked to research hypothesis. By so doing, the study is said to have met its objective.